Institutional Cross-Ownership of Peer Firms and Revelatory Price Efficiency - Cho, Young Jun; Yang, Holly; Zhao, Yue (Journal of Financial and Quantitative Analysis, 2026)
Abstract We argue that cross-ownership increases the amount of private information in stock prices, enhancing the ability of stock prices to provide feedback to managers. Consistent with this argument, we find greater cross-ownership heightens a firm’s investment- q sensitivity. This effect is stronger for firms with a lower propensity for voluntary disclosure and for firms whose managers hold less private information. Furthermore, we find that cross-ownership is negatively associated with the sensitivity of a firm’s investment to its peers’ stock prices. Additionally, cross-ownership has a stronger impact on the investment- q sensitivity when measured among investors who trade more actively in the firm’s shares. By using financial institution mergers as an identification strategy, we strengthen the causal inference. Overall, our results suggest that cross-ownership helps increase revelatory price efficiency (RPE), potentially leading to more efficient corporate decisions.